2021
DOI: 10.1186/s12864-020-07343-x
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation of bone morphogenetic protein-15 (BMP15) causes both infertility and increased litter size in pigs

Abstract: Background Atypical external genitalia are often a sign of reproductive organ pathologies and infertility with both environmental or genetic causes, including karyotypic abnormalities. Genome-wide association studies (GWAS) provide a means for identifying chromosomal regions harboring deleterious DNA-variants causing such phenotypes. We performed a GWAS to unravel the causes of incidental cases of atypically small vulvae in German Landrace gilts. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our meta-analyses approach using imputed sequence variants revealed six QTL of which five were associated with multiple traits. Several porcine pleiotropic loci are underpinned by heterozygous loss-of-function alleles that may have fatal consequences in the homozygous state [ 49 51 ]. Pleiotropic QTL have also been described in pigs for highly correlated traits [ 31 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analyses approach using imputed sequence variants revealed six QTL of which five were associated with multiple traits. Several porcine pleiotropic loci are underpinned by heterozygous loss-of-function alleles that may have fatal consequences in the homozygous state [ 49 51 ]. Pleiotropic QTL have also been described in pigs for highly correlated traits [ 31 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the essential role of BMP15/Bmp15 during the ovulatory period in mammals. Mutant models in mice and pigs, 6,13 as well as natural mutations of the BMP15 gene in humans and sheep, 7,10,11 have been linked with ovulatory defects. Also vaccination against BMP15 using synthetic peptides caused phenotypes in sheep and cattle 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…These species‐specific features reported for BMP15 / Bpm15 mutant variants seem associated to the species' reproductive strategy, generally resulting in more severe ovarian phenotypes in mono‐ versus poly‐ovulatory species 12 . However, a recent study in pig has shown, for the first time, natural BMP15 mutations clearly affecting fertility in a poly‐ovulatory species 13 . In teleost fish (animal group with high egg production capacity), the zebrafish bmp15 knockout is the only mutant model available to date.…”
Section: Introductionmentioning
confidence: 97%
“…Thus far, 35,384 QTLs have been identified in pigs according to pigQTLdb, of which 3315 QTLs are associated with reproduction ( , 25 April 2022). In pigs, GWAS has identified numerous SNPs significantly associated with growth traits [ 4 , 5 ], meat quality [ 6 , 7 ], feed efficiency [ 8 , 9 ], semen traits [ 10 , 11 ], coat color [ 12 , 13 ], genetic defects [ 14 , 15 ], disease susceptibility [ 16 , 17 ], and microbial phenotypes [ 18 ]. However, most of them were genotyped based on SNP microarrays, and the density of markers is a key factor affecting GWAS efficiency [ 19 ].…”
Section: Introductionmentioning
confidence: 99%